Rationality and Knowledge in Religious Discourse: A Critique of Philosophical Relativism - Akaruese, Lucky Oritsetojumi (Obafemi Awolowo University, 2014)
The central focus of this thesis is to make a case for the unity of all discourses irrespective of the said peculiar nature of each discourse. Religious discourse which involves concepts of supernatural or transcendental agencies, has presented special problems in the history of philosophical enquiry and it has often seemed to be a unique area of unquestioned or unfounded beliefs, dogma, superstitions, arbitrary assumptions, etc. An apparent failure to make religion stand up to certain norms of rationality has led to the neo-Wittgensteinian philosophy of religion, as epitomized in the central concepts of the works of Dewi Zephaniah Phillips in which an attempt is made to claim special kind of criteria of meaningfulness for religion.